Isolation and in vitro characterisation of dental pulp stem cells from natal teeth - AKYÜZ, SERAP HATİCE (SPRINGER, 2010)
Dental pulp stem cells were primarily derived from the pulp tissues of exfoliated deciduous teeth, primary incisors and permanent third molar teeth. The aim of this study was to isolate and extensively characterise SCs derived from human natal dental pulp (hNDP). For characterisation, proliferation capacity, phenotypic properties, ultrastructural and differentiation characteristics and gene expression profiles were utilised. A comparison was done between the properties of NDP-SCs and the properties of mesenchymal stem cells (MSCs) from bone marrow (BM) of the human. Stem cells isolated from hNDP and hBM were analysed by flow cytometry, reverse transcriptase-PCR, Real Time-PCR, and immunocytochemistry. Both cell lines were directionally differentiated towards adipogenic, osteogenic chondrogenic, myogenic and neurogenic lineages. hNDP-SCs and hBM-MSCs expressed CD13, CD44, CD90, CD146 and CD166, but not CD3, CD8, CD11b, CD14, CD15, CD19, CD33, CD34, CD45, CD117, and HLA-DR. Ultrastructural characteristics of hNDP-SCs showed more developed and metabolically active cells. hNDP-SCs and hBM-MSCs expressed some adipogenic (leptin, adipophilin and PPAR gamma), myogenic (desmin, myogenin, myosinIIa, and alpha-SMA), neurogenic (gamma-enolase, MAP2a,b, c-fos, nestin, NF-H, NF-L, GFAP and betaIII tubulin), osteogenic (osteonectin, osteocalcin, osteopontin, Runx-2, and type I collagen) and chondrogenic (type II collagen, SOX9) markers without any stimulation towards differentiation under basal conditions. Embryonic stem cell markers Oct4, Rex-1, FoxD-3, Sox2, and Nanog were also identified. The differentiation potential of hNDP-SCs and hBM-MSCs to adipogenic, osteogenic, chondrogenic, myogenic and neurogenic was shown. This report described the first successful isolation and characterisation of hNDP-SCs.
Keywords: Human; Dental pulp; Natal teeth; Bone marrow; Mesenchymal stem cell; In vitro; Characterisation; BONE-MARROW; OSTEOGENIC DIFFERENTIATION; TISSUE; CRYOPRESERVATION; OSTEOBLASTS; POPULATION; SCAFFOLDS; NEURONS; DPSCS